(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2015)
In this paper the origin of the concepts of geometry and the way and the reason for systematization is analyzed. A first approach to the analysis of the processes involved in the development of geometry determines its target and leads us to clarify what is meant by a mathematical object and, further, what is meant by geometric object, and leads into the structure essential geometry.